2022
DOI: 10.3389/fchem.2022.870985
|View full text |Cite
|
Sign up to set email alerts
|

Computational Exploration on the Structural and Optical Properties of Gold-Doped Alkaline-Earth Magnesium AuMgn (n = 2–12) Nanoclusters: DFT Study

Abstract: Using CALYPSO crystal search software, the structural growth mechanism, relative stability, charge transfer, chemical bonding and optical properties of AuMgn (n = 2–12) nanoclusters were extensively investigated based on DFT. The shape development uncovers two interesting properties of AuMgn nanoclusters contrasted with other doped Mg-based clusters, in particular, the planar design of AuMg3 and the highly symmetrical cage-like of AuMg9. The relative stability study shows that AuMg10 has the robust local stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The magic numbers N = 4, 10, and 20 present in these clusters can be perfectly explained by using the spherical Jellium model. [21] Numerous binary clusters are accordingly found to have excellent properties by doping Mg clusters with foreign atoms, [22][23][24][25][26][27] such as magnetic superatoms T MMg 8 (T M = Fe, Co, Ni, and Tc), [28,29] efficient catalysts T MMg 55 (T M = Ti and Nb), [30] high stability cage BeMg 16 cluster, [31] and so on. To some extent, these experimental and theoretical results are significant for the enrichment of magnesium-based clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The magic numbers N = 4, 10, and 20 present in these clusters can be perfectly explained by using the spherical Jellium model. [21] Numerous binary clusters are accordingly found to have excellent properties by doping Mg clusters with foreign atoms, [22][23][24][25][26][27] such as magnetic superatoms T MMg 8 (T M = Fe, Co, Ni, and Tc), [28,29] efficient catalysts T MMg 55 (T M = Ti and Nb), [30] high stability cage BeMg 16 cluster, [31] and so on. To some extent, these experimental and theoretical results are significant for the enrichment of magnesium-based clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The study of magnesium-based clusters has already yielded some interesting results. For example, Xi et al [11] and Li et al [12] studied Sr-and Sr 2doped Mg n (n = 2-12) atoms based on DFT and found that SrMg 9 and Sr 2 Mg 8 have a tower-like structure and higher stability than others. Zhu et al found that AuMg 9 cluster with a kind of double vertex tent structure shows the strongest stability in all AuMg n (n = 2-12) clusters [13].…”
Section: Introductionmentioning
confidence: 99%